Investigation of the Local Recurrence Rate after Colorectal Endoscopic Mucosal Resection: Is Incomplete Polyp Resection Really a Clinically Important Problem? Analysis of the Rationale for the "Resect and Discard" Strategy. (8th January 2019) - Arimoto, Jun; Higurashi, Takuma; Chiba, Hideyuki; Misawa, Noboru; Yoshihara, Tsutomu; Kato, Takayuki; Kanoshima, Kenji; Fuyuki, Akiko; Ohkubo, Hidenori; Nonaka, Takashi; Sato, Takamitsu; Sakai, Eiji; et al.
Abstract : Background/Aims . The "Resect and Discard" strategy is a potentially useful strategy. At present, only the lesion size and accuracy of diagnosis are cited as considerations for clinical adoption of this strategy. On the other hand, histopathology of the resected specimens after Endoscopic Mucosal Resection (EMR) reveals often an unclear or positive-margin status, implying Incomplete Polyp Resection (IPR). If IPR indeed increased the risk of local recurrence, histopathological evaluation of the margin would be indispensable and clinical adoption of this strategy is difficult. The aim of this study is to verify the association between IPR and the risk of local recurrence. Methods . The 1872 polyps and 603 EMR cases in 597 patients who had EMR between May 2013 and May 2014 were enrolled. The local recurrence rate until 3 years after the EMR in cases with the target lesions of the "Resect and Discard" strategy was determined in the negative-margin and IPR groups. Results . The final analysis was performed using the data of 1092 polyps, and 222 were categorized into the IPR group. There were no cases of recurrence in either of the groups. Conclusion . This is the world's first report conducted to examine the correlation of IPR and the local recurrence rate for clinical practice of "Resect and Discard" strategy. There is the possibility that pathological evaluation of the margins after EMR in patients with small polyps can be skipped.